Self-Confidence Among University Students - Rawaa Jaafar Abd Al-Mayahy (Academia Open, 2026)
General Background University education increasingly requires students to possess strong psychological attributes to cope with academic and social demands. Specific Background Self-confidence is a key psychological construct that supports learning, motivation, and academic engagement among university students. Knowledge Gap Despite its importance, limited empirical evidence exists on self-confidence levels among university students across gender and academic specialization in the local context. Aims This study aims to identify the level of self-confidence among university students and examine differences according to gender and specialization. Results The findings indicate measurable levels of self-confidence among students, with statistically significant differences based on gender and academic specialization. Novelty The study applies a self-confidence scale grounded in Bandura’s theoretical framework within a university context. Implications The results provide empirical support for integrating psychological development programs into higher education to support student success. Highlights: University Students Demonstrate Identifiable Levels of Self-Confidence Differences Appear Across Demographic and Academic Categories Bandura-Based Measurement Provides Reliable Assessment Outcomes Keywords: Self-Confidence, University Students, Gender Differences, Academic Specialization, Educational Psychology